2000
DOI: 10.1074/jbc.m906893199
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Bcl-2 Protein by CDC2 Kinase during G2/M Phases and Its Role in Cell Cycle Regulation

Abstract: Although it has been reported that Bcl-2 phosphorylation is associated with certain types of apoptosis, there is much controversy over the functional significance of and the kinases responsible for the phosphorylation. In this study, we examined whether Bcl-2 is phosphorylated by CDC2 kinase, a master regulator of G 2 /M transition in the eukaryotic cell cycle. When CDC2 was activated by okadaic acid in HL-60 cells, Bcl-2 phosphorylation was readily induced. The phosphorylation was correlated with the accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 40 publications
(51 reference statements)
8
83
0
Order By: Relevance
“…Our observation of signi®cantly reduced oocyte maturation as a result of Bcl-2 overexpression is consistent with the ®nding of Bcl-2-dependent accumulation of cells in the human promyelocytic leukemia cell line HL-60 in the G2/M phases of the eukaryotic cell cycle (Furukawa et al, 2000). In the latter study, the cell cycle inhibitory e ect of Bcl-2 was attributed to Bcl-2 phosphorylation by CDC2 kinase.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our observation of signi®cantly reduced oocyte maturation as a result of Bcl-2 overexpression is consistent with the ®nding of Bcl-2-dependent accumulation of cells in the human promyelocytic leukemia cell line HL-60 in the G2/M phases of the eukaryotic cell cycle (Furukawa et al, 2000). In the latter study, the cell cycle inhibitory e ect of Bcl-2 was attributed to Bcl-2 phosphorylation by CDC2 kinase.…”
Section: Discussionsupporting
confidence: 76%
“…Recently reported evidence supports the existence of a Bcl-2-sensitive communication between the ER and mitochondria that involves Ca 2+ and may a ect sensitivity to apoptosis Hacki et al, 2000). In addition to its anti-apoptotic function, Bcl-2 has been implicated in the regulation of cell cycle progression at both the G1 to S transition (Vairo et al, 1996) and the G2/M phases of the mitotic cell cycle (Furukawa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We simultaneously measured cellular content of Bcl-2 family proteins and DNA content in AML cells under unstressed conditions and found that the expression of Bcl-2 peaks in G 2 /M-phase where phosphorylation of Bcl-2 at Ser 70 occurs. 31 Interestingly, Bcl-2 levels increased during G 1 to G 2 progression and the amplitude of Bcl-2 change was larger than that of Bax, suggesting that the cellular Bcl-2/Bax ratio is lowest in G 1 cells. It has been described that, in chronic lymphocytic leukemia cells, decreased Bcl-2/Bax ratios and conformational changes of Bax and Bak are among the early steps of spontaneous apoptosis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Bcl-2 and its phosphorylation are associated with resistance to ABT-737-induced apoptosis in AML (unpublished results), 12 and phosphorylated Bcl-2 has been described to be expressed during G 2 /M-phase. 30,31 It is therefore possible that Bcl-2 levels may change during cell cycle progression and that the relative expression levels may be associated with susceptibility to spontaneous and Bcl-2 inhibitor-induced apoptosis. To address this issue, the cellular content of apoptosis-associated proteins was measured in conjunction with DNA content in unstressed OCI-AML-3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…2A). Bcl-2, an anti-apoptotic protein that is phosphorylated and inactivated by Cdk2 kinase during the G2/M transition in proliferating cells (Furukawa et al, 2000), was dephosphorylated and, hence, activated during C2C12 cell differentiation ( Fig. 2A).…”
Section: Model For Cell Cycle Withdrawal In C2c12 Myoblastsmentioning
confidence: 99%